Bimbingan Pastoral Bagi Jemaat di Era Masyarakat 5.0 - Samuel Herman; Yanto Paulus Hermanto (SANCTUM DOMINE: JURNAL TEOLOGI, 2023)
The era of Society 5.0 represents a period in which advanced technology and humans are increasingly integrated, creating significant transformations in social and cultural life. This article explores the role and challenges of pastoral counseling in the Society 5.0 era. This research employs a qualitative approach, combined with a literature review, to understand the role of pastoral counseling in the context of the Society 5.0 era. In the face of rapid technological advancements and social changes, pastoral counseling plays a key role in assisting congregations in comprehending and responding wisely to the dynamics of Society 5.0. The results of this study identify relevant approaches, such as education on technology and ethics, collaboration with technology experts, and a strong spiritual approach. Pastoral counseling that aligns with Christian values can be a robust source of support for congregations as they navigate meaningful lives in the increasingly complex Society 5.0 era.